“I try to take all the time needed, even if i do not have it!”: Knowledge, attitudes, practices of perinatal care providers in canada about vaccination - Wendy Pringle; Devon Greyson; Janice E. Graham; Ève Dubé; Hana Mitchell; Margaret L. Russell; Shannon E. MacDonald; Julie A. Bettinger (Vaccine: X, 2024)
Objective: Successful clinical conversations about vaccination in pregnancy (pertussis, COVID-19, and influenza) are key to improving low uptake rates of both vaccination in pregnancy and infancy. The purpose of this study was to understand Canadian perinatal care providers’ knowledge, attitudes, and practices around vaccination in pregnancy. Methods: Qualitative interviews with 49 perinatal care providers (nurse practitioner, general practitioner, registered nurse, registered midwife, obstetrician-gynecologist, and family physicians) in 6 of 13 provinces and territories were deductively coded using directed content analysis [1] and analyzed according to key themes. Results: Participants detailed their professional training and experiences, patient community demographics, knowledge of vaccines, views and beliefs about vaccination in pregnancy, and attitudes about vaccine counselling. Providers generally described having a good range of information sources to keep vaccine knowledge up to date. Some providers lacked the necessary logistical setups to administer vaccines within their practice. Responses suggest diverging approaches to vaccine counselling. With merely hesitant patients, some opted to dig in and have more in-depth discussions, while others felt the likelihood of persuading an outright vaccine-refusing patient to vaccinate was too low to be worthwhile. Conclusion: Provider knowledge, attitudes, and practices around vaccination varied by professional background. To support perinatal providers’ knowledge and practices, clinical guidelines should detail the importance of vaccination relative to other care priorities, emphasize the positive impact of engaging hesitant patients in vaccine counselling.